Using mediation to solve disputes with avoiding parties - Carneiro, Davide Rua (2010)
In virtually every environment there is the chance that, sooner or later, a dispute will arise. Disputes can take place in the most different scenarios and concern the most different subjects. With the advent of the telecommunication technologies, disputes also started to take place in virtual environments. In order to settle these new disputes, Online Dispute Resolution tools started to emerge. In this paper we present one of such tools, aimed at supporting mediation between two or more parties. Specifically, this tool looks at past known mediation processes and tries to guide the process into a successful outcome. It targets scenarios in which one or more party exhibits avoiding or uncooperative conflict styles, i.e., the party cannot or is not willing to generate valid proposals for dispute resolution.